Managing mental health challenges faced by healthcare workers during covid-19 pandemic - Greenberg, Neil; Docherty, Mary; Gnanapragasam, Sam; Wessely, Simon (BMJ (Online), 2020)
Neil Greenberg and colleagues set out measures that healthcare managers need to put in place to protect the mental health of healthcare staff having to make morally challenging decisions